Do Non-Performing Loans Deteriorate the Sustainability of the Banking Sector? (KASBIT Business Journal, 2025)
This paper seeks to investigate the enduring influence on Non-Performing Loans (NPLs) due to bank-specific and macroeconomic factors alongwith governance structure within the Pakistani banking sector context during 2011 to 2023. Utilizing OLS and Quantile Regression Models, distinct analyses were conducted for Islamic banks, private banks, and public banks in Pakistan separately. The empirical results indicate that a significant portion of variations in NPL can be elucidated by bank-specific and macroeconomic variables. Islamic banks are less sensitive as compared to private and public banking systems to variability in their NPLs. This unlocks the door for policy makers and practitioners to foresee the future of banking transactions especially the Islamic banks where the ratio of NPLs is minimum.
Keywords: NPLs, Sustainability, Banking Sector Performance, Quantile Regression